Review: Mycoendophytes in medicinal plants: Diversity and bioactivities - MAHENDRA RAI; ANIKET GADE; DNYANESHWAR RATHOD; MUDASIR DAR; AJIT VARMA (Nusantara Bioscience, 2012)
Abstract. Rai M, Gade A, Rathod D, Dar M, Varma A. 2012. Review: Mycoendophytes in medicinal plants: Diversity and bioactivities. Nusantara Bioscience 4: 86-96. Endophytes are microorganisms that reside in internal tissues of living plants without causing any negative effect. These offer tremendous potential for the exploitation of novel and eco-friendly secondary metabolites used in medicine, the pharmaceutical industry and agriculture. The present review is focused on diversity of endophytes, current national and international bioactive secondary metabolite scenario and future prospects. Endophytic fungi as novel source of potentially useful medicinal compounds are discussed along with the need to search for new and more effective agents from endophytes to combat disease problems